IMPLEMENTATION OF HR MANAGEMENT IN INCREASING TEACHER PERFORMANCE AT SDIT AL-FAJRI CAHAYA UMAT CIKARANG TIMUR - Acep Andi Suhendi (Dinasti International Journal of Education Management And Social Science, 2021)
The purpose of this study is to find out and explain the implementation of Human Resource Management (HR) at SDIT Al-Fajri Cikarang Timur. This type of research is descriptive qualitative method with a case study approach that uses detail as well as observation. The results of the analysis found that the HR implementation of SDIT Al-Fajri Cikarang Timur was a) The description of HRM at SDIT Al-Fajri Cahaya Ummah can be seen in the managerial aspects of the principals and teachers. b) The implementation of human resource management at SDIT Al-Fajri Cahaya Ummah includes Man Power Planning (HR Planning), Recruitment & Selection (Recruitment and Selection), HR Placement, Training & Development (Training and Development), Performance Evaluation (Performance Evaluation), and Compensation&Benefit (Compensation and Benefit). Things that still need to be considered are the absence of TNA (Training Needs Analysis) or Training and Development Needs Analysis for teachers and the need to improve teacher welfare. c) In terms of teacher performance at SDIT Al-Fajri Cahaya Ummah, it is quite good, with the activities carried out by teachers both in the classroom during teaching and outside teaching hours. The classroom learning process is carried out according to the applicable curriculum by referring to the syllabus and lesson plans (Learning Implementation Plan). In addition, extracurricular activities such as scouting training, religious affairs, and sports outside class hours are also carried out.